Statistically significant words of four Service Menaia of the 11th century - Baranov, Victor Arkadievich (Slavistica Vilnensis, 2019)
The work deals with experiments on search of keywords in Slavonic Service Menaia of the 11th century by means of three statistic measures — Weirdness, TF*ICTF’ and Log-Likelihood. Statistically significant words are found in the lists of 30 the most frequent lemmas of each copy (three other manuscripts play the role of the alternative subcorpus) and their different assessments by the respective measures are shown. The words that are the most significant due to the assessments done by the three measures on the basis of comparison of the ranks of the lemmas ranked by the values of measures are found in each list. Their comparison with the lists of lemmas that are the most significant on the whole for the collections of hymnographic texts of the corpus “Manuscript” helps to find the keywords in each of the manuscripts. Minimal threshold values of the measures are established for revelation of statistically significant linguistic units. Semantic-thematic interpretation of the keywords gives a possibility of seeing their relationship with the main notions of the Christian church and its realization in each manuscript: Menaion of May — defeat of suffering and death, holiness, praise, joy, Menaion of September — purity, God, Menaion of October — truth, peace, Menaion of November — praise, truth, salvation.